2017
DOI: 10.1021/acsami.6b16556
|View full text |Cite
|
Sign up to set email alerts
|

Impact of PEG Chain Length on the Physical Properties and Bioactivity of PEGylated Chitosan/siRNA Nanoparticles in Vitro and in Vivo

Abstract: PEGylation of cationic polyplexes is a promising approach to enhance the stability and reduce unspecific interaction with biological components. Herein, we systematically investigate the impact of PEGylation on physical and biological properties of chitosan/siRNA polyplexes. A series of chitosan-PEG copolymers (CS-PEG2k, CS-PEG5k and CS-PEG10k) were synthesized with similar PEG mass content but with different molecular weight. PEGylation with higher molecular weight and less grafting degree resulted in smaller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(84 citation statements)
references
References 44 publications
4
78
1
1
Order By: Relevance
“…It is well known that the folic acid receptor is often overexpressed in malignant tissues of epithelial origin, such as ovarian carcinomas [37]. The presence of PEG chains provides an improved stability to nanoparticles [38][39][40] and depending on the N/P ratio knockdown efficiencies from 80% to 95% can be achieved [39]. For HeLa and OV-3 cell lines, higher silencing efficiencies would be expected due to a more efficient targeted cell uptake.…”
Section: In Vitro Transfection Efficiencymentioning
confidence: 99%
“…It is well known that the folic acid receptor is often overexpressed in malignant tissues of epithelial origin, such as ovarian carcinomas [37]. The presence of PEG chains provides an improved stability to nanoparticles [38][39][40] and depending on the N/P ratio knockdown efficiencies from 80% to 95% can be achieved [39]. For HeLa and OV-3 cell lines, higher silencing efficiencies would be expected due to a more efficient targeted cell uptake.…”
Section: In Vitro Transfection Efficiencymentioning
confidence: 99%
“…Different MWs of mPEG (2, 5, and 10 kDa) were conjugated to CS, and it was found that PEG with higher MW and less grafting density is a promising strategy to improve CS/siRNA NP performance both in vitro and in vivo. 20 It was also proved by Chen et al 21 that methotrexate (MTX)loaded mPEG (2000 Da)-conjugated CS NPs could enhance their targeting ability and prolong blood circulation even better than folic acid (FA), a targeting ligand for nanocarriers. 21 MTX {(2S)-2-[[4-[(2,4-diaminopteridin-6-yl)-methylethylamino]benzoyl]amino] pentanedioic acid)} is a stoichiometric inhibitor of dihydrofolate reductase.…”
Section: Introductionmentioning
confidence: 97%
“…In practice nanoparticles have been optimized with various PEG formulations, for example 10 kDa molecular weight PEG best reduced clearance for chitosan/siRNA nanoparticles delivered intravenously, while 1 kDa molecular weight PEG was best for oral administration of prodrug-based micelles. 1617 …”
Section: Peg and Other Synthetic Polymeric Shielding Strategiesmentioning
confidence: 99%